Upaya Peningkatan Prestasi Belajar Dan Keaktifan Siswa Dalam Belajar Pendidikan Agama Islam (Pai) Kelas Ix A Smp Negeri 3 Baureno Kab. Bojonegoro Melalui Penerapan Metode Giving Question And Getting Answer - Nurhayati, Emy (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
By using the providing question and getting answer method, class action research at SMPN 3 Baureno, Bojonegoro Regency seeks to identify a pleasant PAI learning atmosphere. With the emphasis on declarative knowledge in junior secondary school (SMP) PAI learning, this method was determined to be the most effective alternative action. There are three cycles in the action research procedure: planning, observing and implementing, and reflecting. Merely 43.8% of the students, or 14, contributed to the PAI learning process' efficacy in the first cycle. Using this strategy, the number of students increased by 62.5%, or up to 20 students, in the second cycle. In the third cycle, the strategy of asking questions and getting answers contributed 90%, or 28 students, to the efficacy of PAI learning. The outcomes of the formative assessments are directly correlated with the efficacy and activity of PAI learning. As many as 44%, or 14 students, achieved a score higher than 75 in the first cycle. Twenty students received a score higher than 75 in the second round, bringing the total to 62.5%. In the third cycle, the percentage changed to 90.5%, meaning that 28 students had a score higher than 75. The process of asking questions and getting answers has the potential to establish a productive, engaging, and pleasurable learning environment for PAI.